Turn-taking and the structural legitimization of bias: The case of the Ford-Kavanaugh hearing by the United States Senate Committee on the Judiciary. (November 2019) - Raymond, Chase Wesley; Caldwell, Marissa; Mikesell, Lisa; Park, Innhwa; Williams, Nicholas
Abstract: This paper offers an analysis of the Ford-Kavanaugh hearing by the U.S. Senate Judiciary Committee, with particular attention to the role of the Committee chairperson within this procedural infrastructure—an infrastructure that, we argue, systematically provides for and thereby implicitly legitimizes the insertion of bias in its proceedings, while nonetheless orienting to an ideology of fairness based on time limits for speaking. Focusing on the linguistic and interactional mechanisms through which chairpersons may use the 'interstitial spaces' that emerge within such hearings, we conclude that the structural privileges afforded to partisan chairpersons can compromise the Committee's ability to reach impartial and unbiased conclusions in its investigations, and we offer recommendations with regard to how this might be resolved. Highlights: 'Interstitial spaces' can emerge between phases in Committee hearings. Committee chairpersons can make use of these spaces to insert partisan perspectives. There are linguistic and interactional mechanisms that chairpersons can deploy to monopolize use of interstitial spaces. Impartiality (in terms of equal time limits for speaking) is undermined by such interstitially-produced commentaries. Committee members should learn to combat these practices if the role of chairperson is to be filled by the Majority Leader.